ANALISIS EFISIENSI DISTRIBUSI PADA PENJUALAN PRODUK OLAHAN BUAH DAN SAYURAN DENGAN METODE DATA ENVELOPMENT ANALYSIS (DEA) - Silvana Maulidah (Agriekonomika, 2016)
Industrial agro requires efficient marketing distribution making it easier for consumers to get their products and can optimize the benefits to achieve a large market share. The purposes from this research is to identify the distributional channel toward fruit and vegetable processing product sale, to analyze the efficient rate on fruit and vegetable processing product, and to formulate the distributional efficiency rate improvement strategy which is not efficient using Data Envelopment Analysis (DEA) is done by WDEA (Warwick DEA) Software. Limitations in the efficiency measurement in this study is the input and output variables. Input variables include the number of retailers, delivery volume, and distribution costs. Variable output includes the volume of sales, revenue and profits. The result of distributinal efficiency analysis toward fruit and vegetables processing product selling namely: (1) used are zero-rate and one rate distributional channeling. (2) There are 8 distributional channeling which is efficient includes in Malang, Batu, Kediri, Tuban, Magelang, Jombang, Lumajang and Surabaya. Meanwhile 7 distributional channeling area which is not efficient are Blitar, Banyuwangi, Bojonegoro, Trenggalek, Lamongan, Ponorogo, and  Mojokerto. (3) Improvement strategy toward distributional channeling area which is not efficient are explained below: (a) decrease the sending volume according to the efficiency target; (b) increase the selling volume based on the efficiency target in order not to get heaping on product so it can give advantage for industrial agro; and (c) add the total amount of retailer toward distributional area which is not efficient.